2023
DOI: 10.1101/2023.02.07.527576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Junctophilin-2 Regulates Mitochondrial Metabolism

Abstract: Right ventricular dysfunction (RVD) is a risk factor for mortality in multiple cardiovascular diseases, but approaches to combat RVD are lacking. Therapies used for left heart failure are largely ineffective in RVD, and thus the identification of molecules that augment RV function could improve outcomes in a wide-array of cardiac limitations. Junctophilin-2 (JPH2) is an essential protein that plays important roles in cardiomyocytes, including calcium handling/maintenance of t-tubule structure and gene transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Our study focused on two types of inherited cardiomyopathy, HCM and DCM, caused by inherited variants in the JPH2 gene ( Quick et al, 2017 ; Jones et al, 2019 ). JPH2 is a structural protein that connects the PM to intracellular organelles such as the ER/SR and likely also the mitochondria ( Garbino et al, 2009 ; Beavers et al, 2014 ; Prisco et al, 2023 Preprint ). Inherited JPH2 variants associated with HCM cause aberrant transverse tubule organization and deficits in intracellular Ca 2+ handling ( Quick et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study focused on two types of inherited cardiomyopathy, HCM and DCM, caused by inherited variants in the JPH2 gene ( Quick et al, 2017 ; Jones et al, 2019 ). JPH2 is a structural protein that connects the PM to intracellular organelles such as the ER/SR and likely also the mitochondria ( Garbino et al, 2009 ; Beavers et al, 2014 ; Prisco et al, 2023 Preprint ). Inherited JPH2 variants associated with HCM cause aberrant transverse tubule organization and deficits in intracellular Ca 2+ handling ( Quick et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoylation of JPH2 enables binding to lipid raft domains in the PM ( Jiang et al, 2019 ). Moreover, Prisco et al (2023 Preprint ) recently showed that fatty acid oxidation is impaired in human induced pluripotent stem cell–derived cardiomyocytes in which JPH2 was ablated. A recent lipidomic study of surgical myectomy specimens from an HCM patient with symptomatic left ventricular outflow tract obstruction revealed accumulation of free fatty acids, whereas the concentrations of acylcarnitines and free carnitine were markedly reduced ( Ranjbarvaziri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%